Changes of Tissue Factors and Tissue Factor Pathway Inhibitors in the Acute Phase of Cardiogenic Stroke in Patients With Atrial Fibrillation. (18th July 2020) - Chen, Yong-li; Chen, Juan; Yang, Li; Huang, Kui; Ma, Yu; Ren, Ning; Jiang, Hua
Abstract: Background: To investigate changes of tissue factor (TF) and tissue factor pathway inhibitor (TFPI) in the acute phase of cardiogenic stroke in patients with atrial fibrillation (AF). Methods: A total of 152 patients with nonvalvular persistent AF, 103 cardiogenic stroke patients with nonvalvular persistent AF, and 126 cases with noncardiogenic stroke were enrolled. Non-AF patients ( n = 138) without stroke served as controls. The clinical data, biochemical indicators, and plasma levels of von Willebrand factor (vWF), TF, and TFPI were determined. Results: Compared with controls, the plasma levels of vWF and TF were significantly higher, while TFPI and TFPI/TF ratio were lower in noncardiogenic stroke patients (all P < 0.05). Compared with cardiogenic stroke patients, noncardiogenic stroke subjects showed significantly higher plasma vWF and TF levels while TFPI levels and TFPI/TF ratio were significantly lower (all P < 0.05). Compared with AF patients, plasma levels of vWF, TF, and TFPI were higher while TFPI/TF ratios were decreased in the cardiogenic ischemic stroke subjects (all P < 0.05). Logistic regression analysis showed that a lower TFPI/TF ratio was an independent predictor of cardiogenic stroke in patients with nonvalvular AF (odds ratio = 3.78, 95% confidence interval: 1.86–7.31). Conclusions: During the acute stage of stroke, TFPI/TF ratio is decreased in both cardiogenic and noncardiogenic stroke patients while plasma TFPI levels show divergent changes.